(untitled) (Scientific journal of the Fergana State University, 2026)
This article discusses the life path and spiritual legacy of Khoja Arif Revgari. Observations are made about the valuable spiritual legacy left by the founder of the Khojagon tariqat, Abdukhaliq Gijduvani, and his disciple and successor, Khoja Arif Revgari - the work "Arifnama", the wisdom contained in it, and the ideas put forward in these wisdoms, which serve as an important source of spiritual and spiritual education for a person, purifying the soul, reaching the truth, and forming beautiful human qualities. His spiritual legacy has acquired an important role in purifying the human psyche, heart, and inner self, and the teachings of the representatives of the tariqat, the teachings of the Sufi scholars, and their implementation are given, as well as the rashha (path, method) that frees the heart from vices.